Student Satisfaction With On The Performance Of The Mathematics Teachers During The Covid 19 Pandemic - Abdul Latip, Tatang Herman, Turmudi, Elly Sukmanasa (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
One of the quality learning is influenced by teacher performance. Teacher performance is one of the benchmarks for success in the online mathematics learning process today. This research is a descriptive quantitative research with a survey approach, where data is obtained by distributing questionnaires in an online google form to 60 respondents who are students of SMA Islam Al Azhar 21 Sukabumi City. This study aims to provide an illustration that the performance of a teacher in the learning process, especially during the pandemic will have an impact on the level of student learning satisfaction. The results of this study indicate that the level of student satisfaction with the performance of mathematics teachers is in the 81-100% interval, which is 83% with a very satisfied category, while there are three things that need to be improved in the performance of mathematics teachers, namely the use of learning media/tools, teaching is not student-centered and material delivery is not good.